PERAN LEMBAGA KOPERASI TERHADAP UMKM DI TANGERANG SELATAN - Syamsul Mu’Arif; Mohamad Safi’i; Yulianto Yulianto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economy, but often face significant challenges in access to capital, business assistance, and training. Although cooperatives have the potential to become a collective economic vehicle to empower MSMEs, the effectiveness of their role is still not optimal due to low cooperative literacy among MSME actors, stagnation of innovation and digitalization within cooperatives, and weak synergy with other MSME empowerment ecosystems.This Community Service aims to socialize the role of cooperatives in empowering MSMEs, identify factors causing low cooperative literacy and its impact on MSME participation, and analyze the challenges of cooperative innovation and digitalization. This service uses training and education methods, preceded by a preliminary survey to identify the main problems in the target MSME, namely the Witana Harja Sport Center MSME in South Tangerang.The results of the activity showed a significant increase in understanding among the management and business actors of the Witana Harja Sport Center UMKM regarding the importance of the role of cooperative institutions in facilitating access to low-cost capital and supporting business success, especially in small industries. This socialization also succeeded in increasing understanding of the formation and management of good cooperatives based on the principle of family. Therefore, this activity is expected to encourage active participation of UMKM in cooperatives, so as to create economic independence and strengthen the local economic structure. It is recommended that sustainable cooperation be established between UMKM and cooperative actors to support business development for the common welfare and national economic recovery